Personal subrogation in relation to the right of recourse of the insurer and assignment of the claim – cession - Nižić-Peroš, Jadranka (Oeconomica Jadertina, 2021)
The subject of this paper is a review of legislation and case law regarding personal subrogation, recourse obligation and recourse claim of the insurer for payment of insurance compensation as well as determining the amount of payment of recourse claim in civil proceedings before the court and assignment of the claim - cession. The paper starts from the point of view that the terms and institutes of subrogation, recourse and cession are very similar and that they are often identified, so we try to clearly distinguish what exactly the term refers to. In Croatian law, the right of subrogation of the insurer is most often understood as legal personal subrogation where by paying the insurance compensation the insurer assumes the legal position of its insured and consequently enabling the insurer to claim damages against the responsible person . In addition to the above, the paper also considers the statute of limitations for insurers’ recourse rights. Furthermore, the author starts from the point of view that in court proceedings initiated for recourse payment it is necessary for the court expert to clearly determine the parameters based on which the court will be able to assess in a certain percentage the possible contribution of the injured party to the damage towards the plaintiff, namely the insurer.